Camp Harmony Newsletter,
One newsletter (August 14, 1942) from the Japanese American Internment Camp, "Camp Harmony." Residents of Camp Harmony published the first newsletter May 5, 1942, just days after the opening of the Puyallup Assembly Center, and ended with a souvenir edition on August 14, 1942. The newsletter originally began as the community paper of Area A but expanded with issue 4 to cover the entire camp. The newsletter covered WRA and WCCA announcements, camp recreational events, births and other community news. Issues ranged from two to five pages long. This is final copy published at Camp Harmony.